International Corporate Governance at Bellsouth: A corporate scandal in Nicaragua - Harold Silva Guerra (CLIO América, 2015)
This article arises from research of a course in International Corporate Governance of our Ph.D. from the University of St. Gallen (Switzerland) and applied in a company that has suffered a scandal which would affect its operations in Nicaragua. The analysis applied from the KISS Principles of the professor Dr. Martin Hilb of University of St.Gallen. The violations of law that underlie the case described in this paper stem from actions and omissions relating to BellSouth’s subsidiary in Nicaragua, Telefonía Celular de Nicaragua, S.A. This is a reflexion article is only for academic purposes. Keywords: Corporate governance, violations, scandal, KISS principles.